Spit as indictors of waves provenance in the cost of Argentina - Kokot, R.R. (2010)
Three of the biggest barrier spits of Argentina are studied in order to determine the relationship between the coastal planform and littoral dynamics. The studied landforms are the spit of Cabo San Antonio of an age of the 5800 years BP, the north spit of Caleta Valdés with a maximum age of approximately 5700 years BP and El Páramo spit of San Sebastián bay with an inferred age of approximately 6000 years BP. The orientation regarding the coastal planform of the three spits, allows to establish the relationship between landforms and coastal dynamics, being obtained the predominant waves that gave origin to them. Also the possible consequences for the modification or erosion of these landforms, that they would take to the disappearance of coastal environments of significant ecological value and the submergence of some adjacent areas; just as it would happen in Caleta Valdés.